Comparison of Thoracic Radiography in Patients with Moderate COVID-19 with Diabetes Mellitus and without Diabetes Mellitus - Setyani, Reny Luhur; Permatasari, Pinkan Dwi (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2025)
Background: Coronavirus Disease-19 (COVID-19) is still a health problem worldwide, including in Indonesia. Each individual's symptoms are different and can be affected by comorbidities such as Diabetes Mellitus (DM). Diabetes Mellitus is believed to worsen the COVID-19 disease. Therefore, an RT-PCR examination and radiological examination using the Brixia Score are needed to diagnose and evaluate COVID-19 disease. Purpose: To compare thoracic radiography in patients with moderate COVID-19 with DM and without DM at Jakarta Islamic Hospital Pondok Kopi in January – December 2021 by using Brixia Score as a tool to help determine the severity and prognosis of COVID-19 patients. Methods: This study uses analytic observational research, namely, a cross-sectional approach from secondary data using medical records. Statistical test analysis using the independent t-test. Result: From 54 samples of moderate-degree COVID-19 patients at RSIJ Pondok Kopi (24 people without DM and 30 people with DM), It was found that men and women have the same number, namely 12 people (50%). The majority of Brixia scores in the group without DM is 6 – 10, as many as 12 people (50%), while in the group with DM as 11 – 15, as many as 18 people (60%). The group with DM had a higher Brixia Score than those without DM. The thoracic radiography on the lower zone of the group with DM is dominantly alveolar infiltrate. Conclusion: There is a significant difference in the Brixia score of moderate degree COVID-19 patients without DM and with DM (p<0.001).